Institutional Distrust, Institutional Participation, and Protest Behavior in the European Social Movement Sector. Issue 2 (1st December 2019) - Schoene, Matthew
Abstract : Institutional distrust has become a pervasive element of global society in general and European society in particular. Concurrently, participation in institutions is also declining, raising concerns about the effectiveness of civil society. Distrust of institutions like the political, education, legal-judicial, and law enforcement systems is linked to declining participation in mainstream political behaviors like voting, but it is unclear how individuals' trust of and participation in certain institutions affects social movement activity and participation in protest. Here, I use recent European protest movements to better understand the link between institutional distrust, institutional participation, and social protest. Using the 7th wave of the European Social Survey, I construct several multilevel mixed-effects logistic regressions predicting participation in four forms of protest: signing petitions, boycotting products, wearing protest badges, and participating in demonstrations. It turns out that, while institutional distrust is moderately and positively linked to certain forms of protest, those who partake in mainstream political institutions are far more likely to participate in all forms of protest.